Relationship between soil chemistry and 137Cs concentration in sprouting branches of Quercus serrata in the first year after felling - Oonuma, Tetsuo; Hashimoto, Masanobu; Ootsuki, Kouta; Fukuyama, Fumiko; Saito, Naohiko; Iijima, Takeshi; Kumata, Atsushi (Tohoku Journal of Forest Science, 2021)
In October 2018, seven years and six months after the accident at the Fukushima Daiichi Nuclear Power Plant, attempted regeneration of stands of Konara oak(Quercus serrata)in the deciduous broad-leaves forest located about 20 km from the nuclear power plant was carried out. In order to clarify the factors affecting the concentration of 137Cs in individual trees in the same forest area, measurements were taken the following year for 137Cs concentration in sprouting branches, 137Cs concentration in soil, concentration of exchangeable bases and other chemical properties, the length and diameter of sprouting branches collected, the number of sprouting branches per stump, and the cross-sectional area of stumps in the first year after logging, when the effects of fallout on mother trees were considered to be significant. Negative correlation was recognized between 137Cs concentration in sprout branch and the amount of exchangeable K in soil similar to previously reported. As a result of multiple regression analysis, the factor related to the 137Cs concentration of the sprout branch was the largest contribution of exchangeable K, followed by stump cross-sectional area showing a positive correlation. The cross-sectional area of the stump might be considered a noteworthy factor for improving the accuracy of future concentration prediction of forests for mushroom logs.